Tinjauan Hukum Bantuan Pelayanan Kesehatan Dalam Undang-Undang Kebencanaan - Noveyla Hardhaning Tyas (Jurnal MHKI, 2023)
The research has a background that Indonesia as a country with a high potential for disaster risk requires having a legal basis that is in accordance with the times. However, the current disaster law is Law no. 24 which was made in 2007 when the National Disaster Management Agency was first created. In theory, as well as the implementation of disaster management that has been carried out, there should be a lot of improvements that can be improved. Therefore, research related to the legal study of health service assistance in the disaster law has an urgency to be carried out, as part of the contribution of researchers and input on the draft disaster law that needs to be updated.